Quantum dissipative effects for a real scalar field coupled to a time-dependent Dirichlet surface in d + 1 dimensions - Fosco, Cesar Daniel (2024)
We study the dynamical Casimir effect for a real scalar field φ in d+1 dimensions, in the presence of a mirror that imposes Dirichlet boundary conditions and undergoes time-dependent motion or deformation. Using a perturbative approach, we expand in powers of the deviation of the mirror’s surface Σ from a hyperplane, up to fourth order. General expressions for the probability of pair creation induced by motion are derived, and we analyze the impact of space-time dimensionality as well as of the nonlinear effects introduced by the fourth-order terms.